2018
DOI: 10.2174/1566524018666180308110822
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling Protein Overexpression in Metabolic Disease and the Risk of Uncontrolled Cell Proliferation and Tumorigenesis

Abstract: In metabolic diseases such as obesity, metabolic syndrome and type II diabetes, the over-expression of uncoupling proteins (UCPs) in a response to increased reactive oxygen species (ROS) generation by mitochondrial respiratory complexes, and to the excess of free fatty acid (FFA) supply from adipose tissue, may protect cells from oxidative stress, lipotoxicity and in turn from death. UCPs by reducing superoxide anion and H2O2 generation trigger several signals to cell for their adaptation to the lipotoxic micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…As OXPHOS processes generate large quantities of protons that induce important pH alterations, under normal conditions, cardiolipin traps protons within the mitochondrial membrane, minimizing the pH changes (35). The protective mechanism is overridden in tumor cells, leading to mitochondrial activity dysfunction (36). Indeed, as suggested by Kiebiesh et al in tumor cells, lipid and electron transport dysfunctionalities of the mitochondria are hallmarks of metabolic deregulations (37).…”
Section: Tumor Cell Metabolism Is Sustained By Mitochondrial Biochemimentioning
confidence: 99%
“…As OXPHOS processes generate large quantities of protons that induce important pH alterations, under normal conditions, cardiolipin traps protons within the mitochondrial membrane, minimizing the pH changes (35). The protective mechanism is overridden in tumor cells, leading to mitochondrial activity dysfunction (36). Indeed, as suggested by Kiebiesh et al in tumor cells, lipid and electron transport dysfunctionalities of the mitochondria are hallmarks of metabolic deregulations (37).…”
Section: Tumor Cell Metabolism Is Sustained By Mitochondrial Biochemimentioning
confidence: 99%
“…It has been shown that overexpression of UCP2 protected VSMCs against hypertension and other cardiovascular diseases through upregulation of mitochondrial uncoupling [ 28 , 29 ]. Mitochondrial uncoupling plays an important role in regulation of cell function, which decreases mitochondrial ROS generation and metabolic stress [ 30 ]. Here, we found that Ang II treatment increased mitochondrial membrane potential and mitochondrial uncoupling in VSMCs, which was associated with the downregulation of Bcl-xL.…”
Section: Discussionmentioning
confidence: 99%
“…Significant increase in superoxide level following burn injury and oxidative damage to tissues are implicated in inflammation, systemic inflammatory response syndrome, severe injury, infection, sepsis, and multiple organ failure. Recent studies have demonstrated that superoxide induces uncoupling process in mitochondria, and that uncoupling is correlated with UCP-1 expression in different tissues, but not in those not expressing UCPs, such as liver [18][19][20]. The expression of UCP-1 in BAT occurs in mitochondria and is a nucleotide-sensitive process [21].…”
Section: Discussionmentioning
confidence: 99%